(3GdZQjH GdeUfas - (3GdbGSe Hf SdGe GdgQhj GdCROj GdNRGYj, CHh YHjO, J (B224 (3g` s
(3ChdgG (B:s
(3MOKfG CHh GdMSf WGgQ Hf YHO GdYRjR GdQYjfi bGd CHh YHjO GdbGSe Hf SdGe (B: (3SeYJ CHG YeQh GdTjHGfi jbhd (B: (3GdCfha jbGd dgG GdeNGWe s
(3BNQgG (B:s
(3hGdRe eKdg Re jRe hGdJegd (B: (3GdJbOe Je LejY GdOjhGf s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B176 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B101s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdeMehOjI (B- (3HecJHI GdeOjfI GdefhQI GdYGeI(B((3dZI (B9) s
Keywords: (3GddZIs